Echinocystic Acid Inhibits Inflammation and Exerts Neuroprotective Effects in MPTP-Induced Parkinson's Disease Model Mice - Dewei He; Guiqiu Hu; Ang Zhou; Yanting Liu; Bingxu Huang; Yingchun Su; Hefei Wang; Bojian Ye; Yuan He; Xiyu Gao; Shoupeng Fu; Dianfeng Liu (Frontiers Media S.A., 2022)
Parkinson's disease (PD), the second primary neurodegenerative disease affecting human health, is mainly characterized by dopaminergic neuron damage in the midbrain and the clinical manifestation of movement disorders. Studies have shown that neuroinflammation plays an important role in the progression of PD. Excessively activated microglia produce several pro-inflammatory mediators, leading to damage to the surrounding neurons and finally inducing neurodegeneration. Echinocystic acid (EA) exhibits an anti-inflammatory effect in peripheral tissues. However, whether it inhibited neuroinflammation remains unclear. Therefore, the current study investigates the effect of EA on neuroinflammation and whether it can improve PD symptoms through inhibiting neuroinflammation. In our experiments, we discovered that EA inhibited the production of pro-inflammatory mediators in LPS-exposed BV2 cells. Further mechanism-related studies revealed that EA inhibited inflammation by activating PI3K/Akt and inhibiting NF-κB and MAPK signal pathways in LPS-induced BV2 cells. Research revealed that EA eases microglia-mediated neuron death in SN4741 and SHSY5Y cells. In in vivo studies, the results demonstrated that EA improves weight loss and behavioral impairment in MPTP-induced mice. Further studies have revealed that EA inhibited dopaminergic neuron damage and inflammation in the mice midbrain. In conclusion, our study demonstrated that EA inhibits neuroinflammation and exerts neuroprotective effects by activating PI3K/Akt and inhibiting NF-κB and MAPK signal pathways in vivo and in vitro.